Implementasi Promosi, Daya Tarik dan Brand Image terhadap Loyalitas Pelanggan di Margi Coffee - Revalina Jeanne Allen; Adhita Maharani Dewi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to examine how promotions, attractiveness, and brand image influence customer loyalty at Margi Coffee, both individually and collectively. The research subjects in this study are individuals who have visited or purchased products at Margi Coffee. The data used in this study are quantitative, with SPSS 25 serving as the data analysis tool. The sample size consists of 50 respondents. Data collection was conducted using a questionnaire distributed to respondents via Google Forms. The data were analyzed using multiple linear regression analysis. The sampling technique employed was purposive sampling. The dependent variable in this study is customer loyalty, while the dependent variables consist of Promotion, Attractiveness, and Brand Image. The results of the study indicate that simultaneously, all variable – promotion, attractiveness, and brand image – significantly influence purchase satisfaction. Partially, the Attractiveness variable has a positive and significant effect on customer loyalty. Meanwhile, the Promotion and Brand Image variables do not have a significant effect on purchasing decisions when analyzed partially.